Răspuns :
f(x) = ax +b
A,B,C ∈ Gf ⇔ f(10) = -2, f(-3)=1, f(2)=0
f(10) = -2 ⇒ 10a +b = -2
f(-3) = 1 ⇒ -3a + b =1
10a + b = -2 ⇒ b= -2 -10a
-3a + b =1
-3a + (-2-10a) =1 ⇒ -3a -10a = 1+2 ⇒ -13a =3 ⇒ a= -3/13
b= -2 -10 (-3/13) ⇒b= -2 + 30/13 ⇒ b= 4/13
f(x) = ax + b = -3x/13 + 4/13
f(2) = 0 ⇒ -3 × 2 /13 + 4/13 =0 ⇒ -2/13 ≠ 0
⇒ A, B, C, ∉ Gf ⇒ A,B,C, nu sunt coliniare
A,B,C ∈ Gf ⇔ f(10) = -2, f(-3)=1, f(2)=0
f(10) = -2 ⇒ 10a +b = -2
f(-3) = 1 ⇒ -3a + b =1
10a + b = -2 ⇒ b= -2 -10a
-3a + b =1
-3a + (-2-10a) =1 ⇒ -3a -10a = 1+2 ⇒ -13a =3 ⇒ a= -3/13
b= -2 -10 (-3/13) ⇒b= -2 + 30/13 ⇒ b= 4/13
f(x) = ax + b = -3x/13 + 4/13
f(2) = 0 ⇒ -3 × 2 /13 + 4/13 =0 ⇒ -2/13 ≠ 0
⇒ A, B, C, ∉ Gf ⇒ A,B,C, nu sunt coliniare